Rapid organizational change - Bleistein, Steven 1968- (Wiley, 2017)
"A new lean and agile model for more effective change management Rapid Organizational Change gets right to the heart of the change initiative problem, and offers a time- and money-saving solution. The fact that so many change initiatives fail or underperform can be traced back to one major issue: pace. While most change management models stress the importance of timeliness, they remain bound to an organization-wide approach to execution.. By targeting change efforts at specific mid-level layers of management, this book helps you achieve the desired outcome more efficiently while saving time, effort and money. Full of practical advice and real-world examples, this book is your action guide to making change happen in a meaningful way. You'll learn how to continually develop great leadership at the institutional level, and gain real, actionable guidance on putting more women in management positions to help you grab that competitive advantage. Today's disruptive technologies and macro-economic patterns have elevated organizational agility to the rank of survival skill. Change is a constant in business, but it's now coming faster than ever; this book gives you the strategies you need to keep from being left behind. Target mid-level managers for faster change Institute perpetual leadership development outside of HR Correct gender inequality in management positions Utilize your best resources to gain competitive advantage Most change management models have the same inherent problem: by the time new processes and strategies trickle down to every manager and staff member, the opportunity has passed and the change can no longer be effective for its intended purpose. Rapid Organizational Change lays out a new shortcut to help your organization stay out in front"--Publisher.